PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X SEMESTER GENAP SMA NEGERI 1 METRO - Kurniawati Riski; Ningrum Ningrum (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
The CIRC learning model is a collaborative based learning model through a reading and writing approach and oral and written language arts. In the learning process, the model forms a heterogeneous group that is responsible for the group's tasks so that more meaningful understanding and learning are formed. The problem in the research conducted by researchers is "There are still many students who have not experienced mastery learning in the economic learning outcomes of class X students of SMAN 1 Metro in the academic year 2018/2019". From these problems, the formulation of the problem in the study was "the influence of the Cooperative Integrated Reading and Composition (CIRC) learning model on the economic learning outcomes of class X students of SMAN 1 Metro 2018/2019 academic year". The influence of the use of Cooperative Integrated Reading and Composition (CIRC) learning models on the economic learning outcomes of class X students of SMA 1 Metro in school year 2018/2019. This study uses the experimental method (Quasi-Experimental), with the form of experimental design that is the form of The Non-Equivalent Control Group Design. In this design, the experimental class and control groups were not randomly selected but with purposive sampling techniques. Based on the results of the research conducted, the hypothesis is accepted, because the value of t count> t table can be seen in the attachment list G, at a significant level of 5%, namely 12.19> 1.70. Students who were declared complete with Minimum completeness criteria were 75 after being given treatment with a Cooperative Integrated Reading and Composition (CIRC) learning model 24 students or with a percentage of 77.42%, while the students in the unfinished category were seven students or with a percentage of 22, 58%. Thus it shows that there is a positive effect on the use of the Cooperative Integrated Reading and Composition learning model (CIRC) on the results of economic learning of class X students of SMAN 1 Metro 2018/2019 Academic Year. Keywords: Cooperative Integrated Reading and Composition Learning Model (CIRC), Economic Learning Outcomes